2016
DOI: 10.3766/jaaa.15026
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Measures of Temporal Processing and Speech Perception in Cochlear Implant Users

Abstract: Results support the theory that the variability in temporal acuity in CI users contributes to the variability in speech performance. Results also indicate that it is reasonable to use the clinically available RGDT to identify CI users with temporal processing impairments for further appropriate rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 58 publications
3
25
0
1
Order By: Relevance
“…The resulting temporal task is to detect discontinuity of the sound within a single channel i.e., neural activity to pre-gap marker offset compared to neural activity to post-gap marker onset. Within-frequency gap detection thresholds (GDTs) for normal hearing (NH) listeners are typically around 5 ms or less under optimal conditions, e.g., sinusoidal stimuli, long marker durations, and supra-threshold presentation levels (Blankenship et al 2016; Eddins et al 1992; Heinrich and Schneider 2006; Oxenham 2000; Penner 1977; Phillips et al 1998; Plomp 1964). By using pure-tones or narrowband noise, the frequency of the pre- and post-gap acoustic markers can be varied so that they are spectrally distinct, resulting in an across-frequency gap detection paradigm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting temporal task is to detect discontinuity of the sound within a single channel i.e., neural activity to pre-gap marker offset compared to neural activity to post-gap marker onset. Within-frequency gap detection thresholds (GDTs) for normal hearing (NH) listeners are typically around 5 ms or less under optimal conditions, e.g., sinusoidal stimuli, long marker durations, and supra-threshold presentation levels (Blankenship et al 2016; Eddins et al 1992; Heinrich and Schneider 2006; Oxenham 2000; Penner 1977; Phillips et al 1998; Plomp 1964). By using pure-tones or narrowband noise, the frequency of the pre- and post-gap acoustic markers can be varied so that they are spectrally distinct, resulting in an across-frequency gap detection paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…However, a limited number of studies have been completed with across-frequency paradigms, and most were completed with NH participants. Cochlear implant (CI) recipients typically display poorer temporal processing skills, which has been associated with poorer speech outcomes post-implantation (Blankenship et al 2016; Busby and Clark 1999; Muchnik et al 1994; Sagi et al 2009). Therefore, due to the importance of temporal resolution and the similarities between across-frequency gap detection and natural speech, it is reasonable to assume that deficits in across-frequency temporal processing result in poorer speech outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to speech perception, the ability to precisely segregate acoustic information is critical for accurate perception of phonemes which then build to form syllables, words, and sentences (Mauk and Buonomano 2004). Individuals with cochlear implants (CIs) often display poorer temporal processing skills compared to normal hearing (NH) individuals (Blankenship et al 2016; Muchnik et al 1994; Tyler et al 1989). Given the importance of temporal resolution in auditory perception and overall speech understanding, it is reasonable to anticipate that deficits in temporal processing will be associated with poorer speech and language outcomes after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…In NH listeners, within-frequency GDTs have been reported as low as 2-3 ms (Blankenship et al 2016; Eddins et al 1992; Heinrich and Schneider 2006; Phillips et al 1998; Plomp 1964). In contrast, CI recipients display a wide range of GDTs with some individuals performing comparable to their NH peers (Bierer et al 2015; Shannon 1989) and others displaying much larger GDTs (Blankenship et al 2016; Tyler et al 1989; Wei et al 2007). Tyler et al (1989) reported GDTs in CI recipients that ranged from 7.5 to 200 ms and noted that CI recipients with smaller GDTs (< 40 ms) displayed better speech recognition abilities and environmental awareness than individuals with larger GDTs (> 40 ms).…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos analisaram o processamento auditivo temporal em indivíduos com perda auditiva (Liporaci 2009, Matos 2010, com próteses auditivas convencionais (Ferreira et al, 2008;Pinheiro et al, 2012, Viacelli et al, 2016 ou com implante coclear (Campos et al, 2008;Sagi et al, 2010;Sharma e Yadav, 2015;Pham et al, 2015;Duarte et al, 2016;Blankenship et al, 2016;Lima, 2017) e também em casos de surdez unilateral (Nishihata et al, 2012;Matos e Frota, 2013b;Mishra et al, 2015;Santos, 2016) apresentando resultados diversos em seus achados, e em sua maioria piores quando comparados aos ouvintes. Edwards (2003) O estudo dos modelos auditivos centrais em indivíduos implantados e com surdez unilateral, e sua possível relação com as dificuldades (sua auto percepção) no reconhecimento de fala na presença de ruído poderá contribuir para o desenvolvimento de novas estratégias tanto tecnológicas como de reabilitação para a otimização da compreensão da fala em condições de escuta desfavoráveis nos indivíduos com entrada sensorial auditiva monoaural.…”
Section: Introductionunclassified